2017
DOI: 10.1016/j.juro.2016.07.086
|View full text |Cite
|
Sign up to set email alerts
|

Standardized Reporting of Microscopic Renal Tumor Margins: Introduction of the Renal Tumor Capsule Invasion Scoring System

Abstract: KEY OF DEFINITIONS FOR ABBREVIATIONS:Renal tumor enucleation allows for maximal parenchymal preservation. Identifying pseudocapsule integrity is critically important in nephron sparing surgery by enucleation. Tumor invasion into and through capsule may have clinical implications although it is not routinely commented on in standard pathologic reporting. We sought to describe a system to standardize the varying degrees of pseudocapsule invasion and to identify predictors of invasion. Materials and Methods:A mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 27 publications
1
19
3
Order By: Relevance
“…No statistically significant association was found between RTPI pattern and pathological size and stage, whereas a significant association was described for grade and histologic subtype (no RTPI was reported in 31.2% of chromophobe RCCs, 11.1% of papillary RCCs, and 6.4% of clear cell RCCs) [30]. At a multivariate analysis, both tumor histology and higher Fuhrman grade were associated with an increased risk of i-Cap 3 score, with papillary type and Fuhrman grade 4 carrying the highest risk (OR 3.04, 95% CI 1.52-6.09, p = 0.002; OR 14.68, 95% CI 2.16-123.18, p = 0.007) [13].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…No statistically significant association was found between RTPI pattern and pathological size and stage, whereas a significant association was described for grade and histologic subtype (no RTPI was reported in 31.2% of chromophobe RCCs, 11.1% of papillary RCCs, and 6.4% of clear cell RCCs) [30]. At a multivariate analysis, both tumor histology and higher Fuhrman grade were associated with an increased risk of i-Cap 3 score, with papillary type and Fuhrman grade 4 carrying the highest risk (OR 3.04, 95% CI 1.52-6.09, p = 0.002; OR 14.68, 95% CI 2.16-123.18, p = 0.007) [13].…”
Section: Discussionmentioning
confidence: 98%
“…Tumor PC was defined as a thin linear regular hypointense band surrounding the tumor on T2-and T1-weighted images. Similarly to the invasion of PC scoring system (i-Cap), recently developed by Snarskis et al to standardize the histopathology report of tumor PC integrity, we proposed a new classification system to standardize MRI report on PC status: MRI-Cap [13]. MRI-Cap was evaluated on both T2-WI and T1WI + T2WI, and it was defined as follows:…”
Section: Imaging Analysismentioning
confidence: 99%
“…1 The recognition of the importance of PCs led to a proposed standardized PC invasion scoring system to classify PC integrity, as current standard pathological reporting do not routinely report PC integrity. 2 A major component of the fibrous PC is collagen. 3 Collagen, being an abundant Extra-Cellular Matrix (ECM) component, is the strongest and hardest to penetrate by tumor cells.…”
Section: Introductionmentioning
confidence: 99%
“…[ 5 9 ] A recent study showed that renal capsule invasion was independently associated with prognosis, while lymphovascular invasion was not. [ 10 ] Snarskis et al [ 11 ] proposed a system for scoring renal capsule invasion on surgical specimens, but no system exists for imaging, which would be more valuable because this information could be used when planning the treatments.…”
Section: Introductionmentioning
confidence: 99%